Human hepatocyte PNPLA3-148M exacerbates rapid non-alcoholic fatty liver disease development in chimeric mice - Kabbani, Mohammad; Michailidis, Eleftherios; Steensels, Sandra; Fulmer, Clifton G.; Luna, Joseph M.; Le Pen, Jérémie; Tardelli, Matteo; Razooky, Brandon; Ricardo-Lax, Inna; Zou, Chenhui; Zeck, Briana; Stenzel, Ansgar; et al. (Cell reports, 2022)
Advanced non-alcoholic fatty liver disease (NAFLD) is a rapidly emerging global health problem associated with pre-disposing genetic polymorphisms, most strikingly an isoleucine to methionine substitution in patatin-like phospholipase domain-containing protein 3 (PNPLA3-I148M). Here, we study how human hepatocytes with PNPLA3 148I and 148M variants engrafted in the livers of broadly immunodeficient chimeric mice respond to hypercaloric diets. As early as four weeks, mice developed dyslipidemia, impaired glucose tolerance, and steatosis with ballooning degeneration selectively in the human graft, followed by pericellular fibrosis after eight weeks of hypercaloric feeding. Hepatocytes with the PNPLA3-148M variant, either from a homozygous 148M donor or overexpressed in a 148I donor background, developed microvesicular and severe steatosis with frequent ballooning degeneration, resulting in more active steatohepatitis than 148I hepatocytes. We conclude that PNPLA3-148M in human hepatocytes exacerbates NAFLD. These models will facilitate mechanistic studies into human genetic variant contributions to advanced fatty liver diseases.
Gesehen am 07.08.2022